STUDI PENGERINGAN BAMBU DENGAN PEMANFAATAN GAS BUANG ( FLUE GAS ) PEMBAKARAN GERABAH - Taufikul Hadi; I Made Bendiyasa; Rahman Sudiyo (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2019)
The temperature of flue gas from pottery burning is still relatively high, which is around 200oC. It is expected that it can be utilized as a drying medium, for example to dry bamboo. In this study, drying medium used was hot air. The main objective of the study is to evaluate drying parameters which are expected to be applicable for drying bamboo with a flue gas medium from pottery. The dimensions of each bamboo sample were 45 cm length, 8 cm width, and 1 cm thickness. The initial weight of each sample was weighed then it was placed in the drying unit. Subsequently the hot air was flowed into the drying unit. The hot air temperatures used were 60°C, 80°C and 100°C. Every 30 minutes interval, as soon as the oven window was closed, the changes of the bamboo mass were recorded and the temperatures of the dry and wet thermometer were measured. The drying process was carried out until the mass of the bamboo samples were constant. In this study, two type of drying rate were observed, i.e., falling and constant rates. It was observed that constant drying rate was lasting for a short period. The drying bamboo was controlled by both water diffusion in the bamboo and water transfer from the bamboo surface. The effective water diffusion coefficients (Deff) are 0.02 cm2/h for hot air of 60oC, 0.03 cm2/h for 80oC, and 0.08 cm2/h for 100oC.